Latitudinal variation in sexual dimorphism in a freshwater fish group. (6th November 2020) - Sumarto, Bayu K A; Kobayashi, Hirozumi; Kakioka, Ryo; Tanaka, Rieko; Maeda, Ken; Tran, Hau D; Koizumi, Noriyuki; Morioka, Shinsuke; Bounsong, Vongvichith; Watanabe, Katsutoshi; Musikasinthorn, Prachya; Tun, Sein; et al.
Abstract: Tropical animals are characterized by showy ornaments and conspicuous body colours as compared with their temperate relatives. Some recent studies have hypothesized that sexual selection pressures are stronger in the tropics than in the temperate zone. Although negative correlations between latitude and the degree of sexual dimorphism would support this hypothesis, phylogeny should be taken into account in such comparative studies. Comparisons of the degree of sexual dimorphism in body size and fin lengths among species of the Adrianichthyidae, a freshwater fish family having a wide geographical range throughout Southeast and East Asia, revealed that lower latitude species are sexually more dimorphic in all characters than higher latitude species. Phylogenetic generalized least squares analyses using a mitochondrial DNA phylogeny demonstrated that the negative correlations between latitude and the degree of sexual dimorphism become non-significant when phylogeny is considered, but that the variance in the degree of sexual dimorphism is explained not only by phylogeny but also almost equally by latitude. Ancestral state reconstruction indicated that sexual dimorphisms have evolved independently even within major clades. These findings are consistent with the view that tropical species are exposed to stronger sexual selection pressures than temperate species. We discuss possible causes of the latitudinal variation in sexual selection pressure.